INTERNATIONAL EXPERIENCES AS A FRAMEWORK FOR EDUCATIONAL IMPROVEMENT (Web of Teachers: Inderscience Research, 2024)
This article provides a concise analysis of advanced educational structures and practices in countries such as the United States, Germany, and France, as well as modern educational programs. It highlights achievements in their education systems, educational standards, and the current advancements in Uzbekistan's education sector. The study emphasizes the advantages of utilizing international experiences to enhance the efficiency of the education system, offering insights into adopting global best practices for improving educational outcomes and standards.